New targets for Turkish childhood national immunization schedule - Celep, Gökçe (Journal of Surgery and Medicine, 2020)
Aim: The National Immunization Schedule (NIS) of Childhood has high coverage, but the administration of non-NIS vaccines (rotavirus, human papilloma virus, meningococcal, influenza, adult type pertussis vaccines [Tdap]) is not widespread in Turkey, despite recommendations by immunization experts. This report intended to explore the administration rates of these vaccines and their reasons in this province. Methods: This questionnaire based cross-sectional study was conducted in a small city in middle northern Turkey. The target population was the family physicians of this city. The participants filled a survey containing questions about their sociodemographic and professional features and attitudes about non-NIS vaccines via email or telephone interviews. Results: Seventy-eight (72%) of 108 physicians were enrolled in the study. The most and least recommended vaccines in daily practice and for addition to NIS were rotavirus and Tdap vaccines, respectively. The main reason of not administrating non-NIS vaccines was lack of knowledge and experience. Conclusion: Vaccination is the safest and cheapest way of protecting from infectious diseases. Family physicians are the leaders of these procedures in the field. Education should be provided to help them reach current knowledge regarding immunizations. Community pediatricians can provide expert consultation. These vaccines should be covered by social security.